2005
DOI: 10.1186/1476-069x-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Risk of high blood pressure in salt workers working near salt milling plants: A cross-sectional and interventional study

Abstract: Background: Workers working close to salt milling plants may inhale salt particles floating in the air, leading to a rise in plasma sodium, which, in turn, may increase the blood pressure and the risk of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…3 Also, the results of Haldiya et al showed that the prevalence of hypertension and blood pressure was found to be higher in non-brine salt workers occupationally exposed to salt particles in the air of the breathing zone. 4 This is in line with the hypothesis that salt may be absorbed from the respiratory tract after being inhaled. 16,17 or the mucociliary current may transport it to the pharynx, where it is swallowed and can be absorbed from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…3 Also, the results of Haldiya et al showed that the prevalence of hypertension and blood pressure was found to be higher in non-brine salt workers occupationally exposed to salt particles in the air of the breathing zone. 4 This is in line with the hypothesis that salt may be absorbed from the respiratory tract after being inhaled. 16,17 or the mucociliary current may transport it to the pharynx, where it is swallowed and can be absorbed from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 85%
“…The similar procedure occurred in the nearly dried Aral Lake where salt and transformed chemicals caused respiratory diseases, malnutrition, and anemia. 2,4,5 Dried Lake Ebinur in China is another example. It is estimated that 4.8 billion tons of salty dust is being carried from the dried surface of this lake every year.…”
mentioning
confidence: 99%
“…The BP levels in the present study were within the range of other studies. 11,[27][28][29][30] Several urban studies from India have indicated higher prevalence of hypertension among urban women compared with their men counterparts. 5 Several studies reported a marked influence of age on BP in many populations, [31][32][33][34] except in traditional populations.…”
Section: Resultsmentioning
confidence: 99%
“…To prevent the cardiovascular diseases of Korean air crews, Choi and Kim (2013) examined the BMI and cholesterol of 326 workers [12]. Haldiya et al (2005) investigated the BMI, diastolic blood pressure (DBP), and systolic blood pressure (SBP) of 247 salt workers performing tasks close to salt milling plants [13]. Moreover, proof-printing workers who are usually exposed to chemicals are susceptible to cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%